PENGEMBANGAN MEDIA SMARTCARDS PADA MATERI KEBERAGAMAN BUDAYA UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS III UPT SD NEGERI TAMBAKBOYO 1 - Latifatul Muhimmah Tata Kharisma; Fera Dwidarti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop and evaluate the feasibility and effectiveness of Smartcards learning media in improving the learning outcomes of third-grade elementary school students on the topic of cultural diversity. Using a Research and Development (R&D) approach using the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The study involved 25 third-grade students at UPT SD Negeri Tambakboyo 1 as subjects. The Smartcards developed contain images of Indonesian culture, such as traditional regional attire, traditional regional dances, and traditional regional houses, organised in the form of educational games. Validation results by experts indicate that the media meets the criteria for feasibility, with validation scores of 78.7% from subject matter experts, 71.1% from language experts, and 93.33% from media experts. Classroom implementation demonstrated a significant improvement in learning outcomes, with a classical completion rate of 96% and an average N-Gain of 0.576 (effective category). Additionally, feedback from students and teachers indicates that this media is engaging, easy to use, and capable of enhancing active participation in learning. Therefore, Smartcards are deemed a viable and effective learning media, and can serve as an innovative alternative for delivering visual and interactive content. It is recommended that the development of similar media be applied to other topics and different educational levels.